Pattern of high-risk human papilloma virus infection among women with cervical intraepithelial neoplasia - Chowdhury, Mina; Jolly, Rabeya Sultana; Amin, Rogina; Elora, Ashfi Laila; Kader, Mousumi; Afrose, Taslima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Cervical cancer ranks as the fourth most commonly diagnosed cancer and the fourth leading cause of cancer-related deaths in women. The purpose of this study was to assess the pattern of high-risk human papillomavirus (HPV) infection in women diagnosed with cervical intraepithelial neoplasia (CIN). The aim of the study was to evaluate the pattern of high-risk human papillomavirus (HPV) infection among women with cervical intraepithelial neoplasia (CIN). Methods: This descriptive observational study involved 100 patients diagnosed with cervical intraepithelial neoplasia (CIN) at the gynecological oncology unit, department of gynecology and obstetrics, Dhaka Medical College Hospital, Dhaka, Bangladesh, from January 1, 2020, to December 31, 2020. Inclusion criteria comprised married women aged 30 to 60 years with colposcopically diagnosed CIN. Socio-demographic data, medical history, and clinical findings were collected and analyzed using SPSS 22.0. Results: The mean age of the patients was 39.26 years (±6.99), with most being housewives (87%) and a large proportion residing in Dhaka (29%). HPV strains were detected in 67% of histopathologically diagnosed CIN cases, with HPV 16 being the most common strain, found in 67.34% of HPV-positive cases. Additionally, mono-infection was more prevalent than co-infection among HPV-positive patients (61.22% versus 38.8%), with the difference being statistically significant (p<0.05). Conclusions: HPV genotypes 16 and 18, being the most prevalent in this study, highlight the need for targeted HPV vaccines and screening programs tailored to the Bangladeshi population to effectively prevent cervical cancer.